Smart Fish Farm Budidaya Ikan Nila Menggunakan NodeMCU Terintegrasi Berbasis Internet Of Things - Jeki Kuswanto Jeki Kuswanto; Muhammad Koprawir; Anggit Ferdita Nugraha (LPPM Universitas Potensi Utama, 2023)
Fish cultivation technology combined with agriculture is developing rapidly, and many suitable systems have emerged to combine planting media and fish cultivation, one of which is viticulture planting media where this agricultural cultivation system is carried out vertically or in stages in indoor and outdoor scopes. Some processes are still carried out manually, namely watering plants, checking water PH, feeding fish, checking water temperature in ponds, and controlling soil moisture levels, this is done manually. Therefore,. This system is made automated based on IoT (internet of things) is needed to overcome some of these problems by utilizing NodeMCu as a microcontroller which will be connected to soil moisture sensors, temperature sensors, PH meters, DC motors, control and monitoring of watering plants, fish feeding, water condition of water can be done automatically. Smart fish Farm cultivating tilapia and iot (internet of things) based verticulture plants can display appropriate data via a mobile application that can be viewed by the user, starting from the soil moisture level displaying the results of pH levels from 1 to 10 pH levels and displaying pond temperature fish from vulnerable 15 to 32 degrees Celsius and mobile applications can control the fish feed system. Keywords—Internet of things, Smart fish Farm, NodeMCu, Verticulture